A Combination of Novel Microecological Agents and Molasses Role in Digestibility and Fermentation of Rice Straw by Facilitating the Ruminal Microbial Colonization - Ma, Yulin; Chen, Xu; Khan, Muhammad Zahoor; Xiao, Jianxin; Cao, Zhijun (Frontiers in Microbiology, 2022)
In the current study, we evaluated the microecological agents (MA) combination with molasses (M) on the biodegradation of rice straw in the rumen. Rice straw was pretreated in laboratory polyethylene a 25 cm x 35 cm sterile bags with no additive control (Con), MA and MA + M for 7, 15, 30 and 45 days and then the efficacy of MA + M pretreatment was evaluated both in vitro and in vivo. The Scanning electron microscopy, X-ray diffraction analysis and Fourier-transform infrared spectroscopy, respectively results showed the MA or MA + M pretreatment altered the physical and chemical structure of rice straw. Meanwhile, the ruminal microbial attachment on the surface of rice straw was significantly increased after MA+M pretreated. Furthermore, the MA + M not only promoted rice straw fermentation in vitro but also improved digestibility by specifically inducing rumen colonization of Prevotellaceae_UCG-001, Butyrivibrio and Succinimonas. Altogether, we concluded that microecological agents and molasses could be the best choice as a biological pretreatment for rice straw to enhance their nutritive value as a ruminant’s feed.